The Effect of Venn Diagram Vocabulary Graphic Organizer on Vocabulary Mastery of the First Year Students of SMP Negeri 23 Pekanbaru - Pratama, Wahyu Putra; Aruan, Rumiri Rotua; Syarfi, M (Indonesian Journal of Education and Development Research, 2025)
This study aims to determine the effect of Venn Diagram Vocabulary Graphic Organizer on Vocabulary Mastery of the first-grade students of SMP Negeri 23 Pekanbaru in the 2024/2025 academic year. The research employed a one-group pretest-posttest design as part of a pre-experimental quantitative method. A sample of 40 students from class VII F was selected through cluster random sampling. Data were collected using vocabulary tests administered before and after the treatment. The treatment consisted of four meetings during which students used Venn Diagrams to compare and contrast vocabulary items based on physical characteristics. The results showed a significant improvement in students' vocabulary mastery, with the mean score increasing from 58.90 in the pretest to 76.60 in the post-test. A paired sample t-test revealed a significance value of 0.000 (   0.05), indicating that the Venn Diagram had a statistically significant effect. The findings suggest that Venn Diagrams can be an effective and engaging tool for improving vocabulary acquisition in junior high school learners. This technique also encourages student interaction and active learning, making vocabulary instruction more meaningful and enjoyable.